Integrative Genomics Sheds Light on Evolutionary Forces Shaping the Acidithiobacillia Class Acidophilic Lifestyle - González-Rosales, Carolina; Vergara, Eva; Dopson, Mark; Valdés, Jorge H.; Holmes, David S. (Frontiers in Microbiology, 2022)
Extreme acidophiles thrive in environments rich in protons (pH values < 3) and often high levels of dissolved heavy metals. They are distributed across the three domains of the Tree of Life including members of the Proteobacteria. The Acidithiobacillia class is formed by the neutrophilic genus Thermithiobacillus along with the extremely acidophilic genera Fervidacidithiobacillus, Igneacidithiobacillus, Ambacidithiobacillus, and Acidithiobacillus. Phylogenomic reconstruction revealed a division in the Acidithiobacillia class correlating with the different pH optima that suggested the acidophilic genera evolved from an ancestral neutrophile within the Acidithiobacillia. Genes and mechanisms denominated as “first line of defense” were key to explaining the Acidithiobacillia acidophilic lifestyle including preventing protons influx that allows the cell to maintain a near neutral cytoplasmic pH and differs from the neutrophilic Acidithiobacillia ancestors that lacked these systems. Additional differences between the neutrophilic and acidophilic Acidithiobacillia included the higher number of genes copies in the acidophilic genera coding for “second line of defense” systems that neutralize and/or expel protons from cell. Gain of genes such as hopanoid biosynthesis involved in membrane stabilization at low pH and the functional redundancy for generating an internal positive membrane potential revealed the transition from neutrophilic properties to a new acidophilic lifestyle by shaping the Acidithiobacillaceae genomic structure. The presence of a pool of accessory genes with functional redundancy provides the opportunity to “hedge bet” in rapidly changing acidic environments. Although a core of mechanisms for acid resistance was inherited vertically from an inferred neutrophilic ancestor, the majority of mechanisms, especially those potentially involved in resistance to extremely low pH were obtained from other extreme acidophiles by horizontal gene transfer (HGT) events.